Implementasi Sistem Informasi Enterprise Pendaftaran dan Registrasi Siswa di Sekolah Menengah Kejuruan Swasta Kabupaten Bandung - Muhammad Prakarsa A.S; Sofia Dewi (Jurnal Accounting Information System (AIMS), 2021)
Implementation of Enterprise Information System Registration and Registration of new Students is a business process in Vocational High School Education, the need for dynamic data collection is a problem that must be solved by unified modelling languange (UML) scheme, a system that can be flexible and responsive. Data integration needs are the ultimate goal of an information system to be able to process data, both for its own needs and to display information to the relevant part in terms of user and data needs for other information systems. In addition, the results of the admission selection of new students are more accurate and prospective students are accepted in accordance with the expected results.